The Perceptions of Medical School Students and Faculty Toward Obesity Medicine Education: Survey and Needs Analysis - Metcalf, Mary (JMIR Med Educ, 2017)
BACKGROUND: Recent trends in obesity show that over two-thirds of US adults are considered at least overweight (body mass index, BMI≥25 kg/m(2)) and of those, about one-third are categorized as obese (BMI≥30 kg/m(2)). Physicians can address the health impacts of obesity; yet research has suggested that physicians-in-training frequently fail to recognize obesity, are not properly educated regarding treatment options, and spend relatively little clinic time treating obesity. Medical school is a unique opportunity to address this area of need so that the doctors of tomorrow are prepared to treat obesity appropriately. OBJECTIVES: The objective of this study was to determine perceptions of where clinical training for medical students on the topic of obesity and its treatment should improve and expand so that we could address the needs identified in a computerized clinical simulation. METHODS: We conducted a literature review, as well as a needs analysis with medical school students (N=17) and faculty (N=12). Literature review provided an overview of the current state of the field. Students provided input on their current needs, learning preferences, and opinions. Faculty provided feedback on current training and their perceptions of future needs. RESULTS: Most students were familiar with obesity medicine from various courses where obesity medicine was a subtopic, most frequently in Biochemistry or Nutrition, Endocrinology, and Wellness courses. Student knowledge about basic skills, such as measuring waist circumference, varied widely. About half of the students did not feel knowledgeable about recommending weight loss treatments. Most students did not feel prepared to provide interventions for patients in various categories of overweight/obesity, patients with psychosocial issues, obesity-related comorbidities, or failed weight loss attempts. However, most students did feel that it was their role as health professionals to provide these interventions. Faculty rated the following topics as most important to supplement the curriculum: patient-centered treatment of weight, bringing up the topic of weight, discussing weight and well-being, discussing the relationship between weight and comorbidities, and physician role with overweight or obese patients. CONCLUSIONS: A review of the literature as well as surveyed medical students and faculty identified a need for supplementation of the current obesity medicine curriculum in medical schools. Specific needed topics and skills were identified.